C/T Merge Locations for Focus - Motaoanyane, Virginia (Linguistica Atlantica, 1998)
Romanian constructions with preverbal focus compared with English clefts point to a parametric approach: languages display different strategies for overt movement to focus according to their parametric setting for [wh/focusl or [tense/focusl. The analysis of [focusl as syntactically dependent on [whl or [tensel provides a uniform treatment for important variation in focus constructions (e.g., preposing through clitic doubling chains versus clefting) and in interrogative clauses (e.g., presence versus absence of V2 effects in embedded interrogatives).